If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + 3 = 30 Reorder the terms: 3 + T = 30 Solving 3 + T = 30 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + T = 30 + -3 Combine like terms: 3 + -3 = 0 0 + T = 30 + -3 T = 30 + -3 Combine like terms: 30 + -3 = 27 T = 27 Simplifying T = 27
| R/10=120 | | -1.8/21.6=-3/n | | 16+5x=20+3x | | 16+5x=10+3x | | Y+3*3=3*3 | | -0.02x=-12 | | F/4=1/2 | | 14+5x=18+3x | | 160/t=20 | | 2(5+3)=10+6 | | (2,4*10^-12)/256 | | S/3=5/3 | | 45+40x=85+30x | | -5x-17=5x-7 | | x^2+y^2+20y=0 | | 100/114.5 | | b+2=2b-3 | | (X+45)=(4x) | | 2(n+2)+8(n-5)= | | 2(n+6)+9(n+6)= | | 50=5/y | | (3x+3)(x+9)= | | 3x^2+3y^2+60y=0 | | 3-3(6-5x)=0 | | (2x-10)=(x+30) | | 2x-9x=28-8x | | x*x+4x=10 | | 2.49xX=.20 | | -3x=-990 | | g(x)=2x^2-4x | | -1+7x+3x=39 | | 6(4x+5)=(8x-1) |